Hubungan Komunikasi Interpersonal Anak Dengan Orang Tua Terhadap Konsep Diri Peserta Didik SD Negeri 1 Bandar Putih Tua Kabupaten Lampung Tengah - Ambar Ambar Adia Safitri; Qomario Qomario; Putry Agung (Gayaku Publisher, 2022)
This study aims to determine whether there is a relationship between interpersonal communication between children and their parents on the self-concept of students at SD Negeri 1 Bandar Putih Tua. This research was conducted in June 2022 at SD Negeri 1 Bandar Putih Tua, Central Lampung Regency. This type of research is quantitative research. The population in this study were third graders at SD Negeri 1 Bandar Putih Tua, Central Lampung Regency, and the sample used was 23 children. Data collection techniques using a scale with 4 alternative answers. The validity test uses the construct validity of the instrument item analysis, while the reliability test uses Cronbach's Alpha with the help of SPSS 16.0 for windows. The data analysis technique uses product-moment correlation analysis. The results showed that interpersonal communication between children and their parents was in the moderate category of 86.96% and students' self-concept was also in the medium class of 869.6%. The results of hypothesis testing obtained count > table that is 0.552 > 0.431 with a significant level of 0.006 <0.05, then H_O is accepted and H_I is rejected. The correlation coefficient of interpersonal communication between children and their parents on self-concept is in the medium category. So it can be said that there is a relationship of interpersonal communication between children and their parents on the self-concept of students at SD Negeri 1 Bandar Putih Tua, Central Lampung Regency.